IDENTIFICATION OF POTENTIAL SITES OF LANDFILLS BY GEO-SPATIAL TECHNIQUES: A CASE STUDY AL-DAWAYA QADHAA, DHI QAR, IRAQ - Mukhalad N. Altai; Faisel G. Mohammed; Mourtadha Sarhan Sachit; Ayaat K. Alzaidy (Journal Park Publishing, 2024)
This study aims to use the geographic information system as an auxiliary technology to select and identify sites for sanitary landfills, in addition to selecting new future sites, determining the suitability of the lands of the city of Al-Dawaya to create sanitary landfill sites, and producing digital maps of the best sites through a set of main criteria such as (Groundwater depth, rivers, urban areas, roads, villages, schools, elevation, power plants, slop, water surfaces, land use, gas pipes, electricity lines, oil pipelines, and wells).Using the data available about the city of Al- Dawaya and assistive techniques such as tools such as geographic information systems and remote sensing, standards were derived for the study area and transformed into a set of maps that represent geological, social and economic standards and environmental considerations, which were processed through the use of tools for spatial analysis, In order to create a suitable indicator map, the weighted linear combination (WLC) approach and the Straight Rank Sum (SRS) method from multi-criteria decision-making were employed. The weights were then derived using the pair-wise comparison method. Two viable locations for the sanitary landfill were chosen after analyzing the data produced by integrating the two maps using geographic information systems to determine the percentage of pixels for compliance and non-conformity. When creating acceptable sites using geographic information systems, the act of confirming the results is a crucial and critical step. The study of fifteen identified criteria was used to accomplish the verification. The first site (A) has an area of (0.80) Km2, while the second site (B) has a total area of (0.99) Km2, and the third site (C) has an area of about (1.40) Km2 square kilometers, these sites are deemed proposed, and the selection procedure is for the decision-maker to select the most suited site. This study provides a method for determining the optimum sites as well as valuable assistance to decision makers in selecting viable sites for sanitary landfills.
Keywords: sites, GIS, Analytic Hierarchy Process (AHP), Straight Rank Sum (SRS) Method.